2013
DOI: 10.1111/1758-2229.12052
|View full text |Cite
|
Sign up to set email alerts
|

Do the honeybee pathogens Nosema ceranae and deformed wing virus act synergistically?

Abstract: The honeybee pathogens Nosema ceranae and deformed wing virus (DWV) cause the collapse of honeybee colonies. Therefore, it is plausible that these two pathogens act synergistically to increase colony losses, since N. ceranae causes damage to the mid-gut epithelial ventricular cells and actively suppresses the honeybees’ immune response, either of which could increase the virulence of viral pathogens within the bee. To test this hypothesis we exploited 322 Hawaiian honeybee colonies for which DWV prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
5
31
1
Order By: Relevance
“…However, there is an evident risk of disease spreading as a result of the intense colony movement between most regions in the Iberian Peninsula. In this sense, the increased prevalence of pathogens in Spain during the study period is not surprising, consistent with data found in other studies (Higes et al 2010a, b;Botías et al 2012;Martín-Hernández et al 2012;Muñoz et al 2014) and in other regions (Fries 2010;Traver and Fell 2011;Martin et al 2013;Bekele et al 2015). It is noteworthy that around 74 % (2006) or 86 % (2010) of the colonies presented at least one of the searched pathogenic agents (V. destructor, N. apis, and N. ceranae) showing N. apis a lower prevalence even though the samples were obtained in Spring, the peak season for N. apis infestation (Fries 2010).…”
Section: Discussionsupporting
confidence: 92%
“…However, there is an evident risk of disease spreading as a result of the intense colony movement between most regions in the Iberian Peninsula. In this sense, the increased prevalence of pathogens in Spain during the study period is not surprising, consistent with data found in other studies (Higes et al 2010a, b;Botías et al 2012;Martín-Hernández et al 2012;Muñoz et al 2014) and in other regions (Fries 2010;Traver and Fell 2011;Martin et al 2013;Bekele et al 2015). It is noteworthy that around 74 % (2006) or 86 % (2010) of the colonies presented at least one of the searched pathogenic agents (V. destructor, N. apis, and N. ceranae) showing N. apis a lower prevalence even though the samples were obtained in Spring, the peak season for N. apis infestation (Fries 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The hypothesis that, through active suppression of the immune response in honeybees and through damaging midgut epithelial cells, N. ceranae creates propitious conditions for viral infection was not been proven in our study. As in other studies (Costa et al, 2011;Martin et al, 2013), the mean number of N. ceranae spores in the colonies in which DWV was detected did not differ from the scale of N. ceranae infection in the colonies free from DWV (MannWithney U test, n = 1681, p = 0.467). Additionally, the percentage of N. ceranae-positive colonies with DWV did not significantly differ from the percentage of colonies without N. ceranae in which DWV was also found (Chi 2 , p = 0.278).…”
Section: Epidemiological Situationsupporting
confidence: 81%
“…has not only arisen from a higher expansiveness (virulence) of N. ceranae Paxton et al, 2007) but also from a discontinued fighting off of nosemosis as a result of the ban on the use of fumagillin in the EU. A considerably higher extent of N. ceranae than of N. apis, has already been reported from other European countries, such as France (Chauzat et al, 2007), Hungary (Tapaszti et al, 2009), Spain (Botias et al, 2012, the Balkan countries (Tlak Gajger et al, 2010;Stevanovic et al, 2011), as well as from North America (the US and Canada) (Chen et al, 2008;Traver and Fell, 2011;Copley et al, 2012;Martin et al, 2013). In Hawaii as well as Croatia, N. ceranae is the only species of Nosema found to infect bee colonies.…”
Section: Epidemiological Situationmentioning
confidence: 77%
“…Viral infections are the least understood of honeybee diseases, due to the lack of information on the mechanisms underlying potential disease outbreaks and limited experimental data available on their different modes of spread, transmission, and persistence [3]. Honeybee colony losses have occurred in Europe and America that cannot be attributed to the Varroa mite ( Varroa destructor ), so an unknown combination of stressors is suspected to be the cause, including other pathogens [1,2,4]. Thus knowledge of the spreading mechanism and synergistic effect of different pathogens within the hives is crucial for understanding bee disease dynamics [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Synergistic effect between microsporidia fungal pathogen Nosema apis and several honey bee viruses such as filamentous virus (FV), bee virus Y (BVY) and black queen cell virus (BQCV) were reported years ago [22], while no association was found between Nosema ceranae ( N. ceranae ) and deformed wing virus (DWV) [4,23]. The infection of the midgut epithelium occurs per os when the honey bee ingests food contaminated with N. ceranae spores [24].…”
Section: Introductionmentioning
confidence: 99%